Gender Inequality and its Impact on Women’s Reproductive Health Status - Abimulyani, Yumi; Nurrachmawati, Annisa (Oshada, 2026)
Gender inequality remains a fundamental barrier to achieving optimal reproductive health outcomes for women globally. This literature review synthesizes current evidence examining the multifaceted relationship between gender inequality and women's reproductive health status across diverse geographic contexts. A comprehensive review was conducted analyzing peer-reviewed studies published between 2021-2025 that examined gender inequality and reproductive health outcomes. The evidence reveals that gender inequality consistently correlates with poor reproductive health outcomes through three primary mechanisms: male-dominated decision-making power over healthcare access, unequal resource distribution and workload burdens, and early discrimination including child marriage. Studies from Tanzania, Morocco, Pakistan, Bangladesh, India, and Uganda demonstrate that women with limited decision-making autonomy experience substantially higher rates of unintended pregnancies, lower contraceptive use, and unsafe delivery practices. Educational inequality and economic marginalization further compound these effects by restricting women's knowledge of reproductive rights and limiting access to sexual and reproductive health services. Gender inequality operates independently of poverty as a determinant of reproductive health, though the two often intersect to create compound vulnerabilities. The evidence points toward solutions including women's education, community programs challenging restrictive gender norms, economic empowerment interventions, and policy frameworks promoting gender equality. Gender inequality fundamentally undermines women's reproductive rights and choices, contributing to increased maternal and infant morbidity and mortality. Strengthening gender equality through education, decision-making empowerment, and economic access represents a critical pathway to improving women's reproductive health outcomes globally.